Dataset: Polarisation-controlled single photon emission at high temperatures from InGaN quantum dots - Wang, T; Puchtler, T (University of Oxford, 2017)
The data was taken with temperature-dependent time-integrated, time-resolved, and polarisation-resolved microphotoluminescence, and Hanbury Brown and Twiss experiments from 5 to 250 K. The purpose is to investigate whether non-polar a-plane quantum dots can act as high temperature single photon sources with optical polarisation control beyond the 200 K Peltier cooling threshold. All data were taken during April-May 2016.